DEVELOPMENT STRATEGY FOR PRIVATE BICYCLE TRANSPORTATION AT UNHAS TAMALANREA CAMPUS - Ahmad, Syarifah Nuzul; Yamin Jinca, Muhammad; Kumala D.S, Yashinta (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
With various activities of the academic community and the community, it will certainly affect the movement of transportation in the Unhas Campus Area. Various characteristics of motorized and non-motorized vehicles located on one road section will cause congestion, noise and pollution. These transportation problems can interfere with comfort, safety, and security while on the move, For this reason, in the construction and development of infrastructure at the Unhas Campus, it is necessary to apply sustainable and environmentally friendly transportation, bicycles have many benefits, including health, economic, and environmental benefits. This study aims to determine how the effectiveness of bicycle lanes, bicycle transportation facility services, and the concept of bicycle transportation development that can be applied at the Unhas Tamalanrea Campus. The analysis method used is SWOT Analysis. Data collection was conducted through observation, interviews, and questionnaires. The respondents taken were cyclists at Unhas Tamalanrea Campus using axial sampling techniques. The results showed that the condition of bicycle transportation facilities at Unhas Tamalanrea Campus was quite good but still needed to be improved in accordance with the guidelines and concepts of campus bicycle transportation.